2016
DOI: 10.1111/bjh.14379
|View full text |Cite
|
Sign up to set email alerts
|

Survival differences between patients with Hodgkin lymphoma treated inside and outside clinical trials. A study based on the EORTC‐Netherlands Cancer Registry linked data with 20 years of follow‐up

Abstract: SummaryThe survival of patients diagnosed with Hodgkin lymphoma (HL) has improved from 70% to 90% in clinical trials. However, population-based data has shown lower survival. In this study, clinical trial data were linked with cancer registry to identify trial and non-trial participants and differences in overall survival and associated factors were assessed. In 1986-2004, 27% of HL patients aged 15-70 years participated in clinical trials. Compared to non-trial participants, trial participants were younger (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 33 publications
3
31
0
2
Order By: Relevance
“…The PFS curves of the real-world ABVD patients and RATHL trial patients, aged younger than 60 years, are remarkably similar in both the absolute 5-year estimates of progression-free survival and in the kinetics of relapse. This is observed in both the whole ABVD cohort and IPS 3+ subgroup, and is consistent with data published from the Netherlands that suggest similar outcomes are achieved for HL patients who are treated within or outside of clinical trials [7].…”
Section: Discussionsupporting
confidence: 90%
“…The PFS curves of the real-world ABVD patients and RATHL trial patients, aged younger than 60 years, are remarkably similar in both the absolute 5-year estimates of progression-free survival and in the kinetics of relapse. This is observed in both the whole ABVD cohort and IPS 3+ subgroup, and is consistent with data published from the Netherlands that suggest similar outcomes are achieved for HL patients who are treated within or outside of clinical trials [7].…”
Section: Discussionsupporting
confidence: 90%
“…An alternative approach to collecting long‐term follow‐up data from clinical trial participants is to initiate prospective observational studies based on population‐based cohorts that represent real‐world survivors. Collaborating with population scientists and their databases where patients are actively followed can greatly improve the efficiency of outcomes research (Liu et al ., , ; van de Poll‐Franse et al ., ; Thong et al ., ).…”
Section: Determinants Of Health‐related Quality Of Life Of Cancer Surmentioning
confidence: 99%
“…Although recent clinical trials using risk‐adapted treatments and novel salvage strategies have demonstrated a significant improvement in the outcomes of patients with advanced‐stage HL, it is important to note that such results are only applicable to carefully selected patients who would meet the inclusion criteria for such trials . This was even demonstrated in a recent study that highlighted the differences in baseline characteristics of the patients enrolled versus not enrolled in clinical trials to be an important determinant of outcomes in patients with HL . Hence, it is crucial to understand the limitations of applicability of these advances at the population level and how they influence “real‐world” outcomes.…”
Section: Discussionmentioning
confidence: 99%